Editors’ Introduction to the Special Issue on ‟Superintelligence” - Carey, Ryan; Maas, Matthijs; Watson, Nell; Yampolskiy, Roman (Informatica, 2017)
We summarize the contents of this special issue, which contains four papers on strategic issues surrounding superintelligence, and three papers proposing concrete directions for future research.